Analisis Perilaku Masyarakat dalam Pencegahan Demam Berdarah Dengue di Puskesmas Tanjung Baru Ogan Komering Ulu Tahun 2021 - Aprilia Atika; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Dengue hemorrhagic fever is a disease caused by the bite of the Aedes aegypti mosquito which can cause illness and death. The purpose of this study was to find out what factors were related to community behavior in preventing dengue hemorrhagic fever. The design of this study was Cross Sectional. The population in this study is the community who seek treatment at the Tanjung Baru Health Center, Ogan Komering Ulu Regency in 2021. The sampling method in this study uses the purposive sampling technique. The sample of this study was determined by using the Lemeshow formula, totaling 35 respondents. Data collection by using a questionnaire. The results of the statistical analysis of respondents using the Chi-Square test showed that there was a significant relationship (p < 0.05) for knowledge (P Value 0.028), cleanliness of the home environment (P Value 0.012), implementation of 3 M (P Value 0.004). Meanwhile, there was no significant relationship (p>0.05) for age (P Value 0.115), attitude (P Value 0.251), use of insect repellent (P Value 0.283) and staff support. (P Value 0.27). From the results of the multivariate analysis, the dominant factor on community behavior in preventing dengue hemorrhagic fever, was the cleanliness of the home environment (P Value 0.022) (OR 0.17). This research , it is hoped that the Puskesmas will provide counseling about dengue hemorrhagic fever, conduct regular fogging in an effort to prevent dengue fever and optimally implement programs related to infectious diseases